The Application of Fuzzy Logic in Optimization Pulp in Pt.Toba Pulp Lestari, Tbk With the Mamdani Method - Dony Pakpahan; Putri Khairiah Nasution (JMEA : Journal of Mathematics Education and Application, 2023)
Fuzzy logic is used to show data or information that is certain. This survey examines the used of fuzzy logic in optimizing production pulp at PT. Toba Pulp Lestari, Tbk using the Fuzzy-Mamdani approach. Constraints faced include the uncertain amount of pulp production from time to time . The steps in solving these problems, namely: (1) is to form a fuzzy set and determine the conversation. Next, (2) is to find out the fuzzyfication that changes the input into fuzzy. Next, (3) is the formation of fuzzy rules with the max method. (4) is defuzzification with MOM method. The problem solving is assisted with the assistance of the Matlab software application. The data in this study are the quantity of production, the quantity of stock and the number of requests from January 2021-December 2021. Based on the data obtained using the Mamdani method, it is known that the optimal production based on the amount of demand and supply is January 13,300 ton, February 18,200 ton, March 8,110 ton, April 10,700 ton, May 10,600 ton, June 13,400 ton, July 12,000 ton, August 10,700 ton, September 18,800 ton, October 18,300 ton, November 10,100 ton, December 10,400 ton.